PENDAMPINGAN DAN PEMBERDAYAAN PENGELOLAAN KEUANGAN PADA LPD DESA ADAT CEPAKA - I Ketut Yudana Adi; Kukuh Rian Setiawan; Ida Ketut Kusumawijaya (Synergy and Society Service, 2021)
Covid 19 pandemic has a huge impact on the Cepaka Village Community, starting from the closure of the tourism sector for foreign tourists, SMEs with low orders, culinary selling products with a low cost strategy, jogging tracks and bicycle tracking which are crowded with domestic tourists, cannot provide economic benefits, so does not give value to farmers who own rice fields that are traversed by cycling tourists or tourists who jog and take selfies as well as the financial behavior of rural communities that tends to be consumptive, causing the Cepaka Village community to not be economically prosperous. The focus of this activity is carried out based on this grouping, namely Creating, packaging / packaging tourism villages by involving all existing potentials, and involving the village community. Management / governance of UKM and services that will be the core products of tourism villages and the impact of tourism villages, and Carry out assistance activities for community financial institutions in cooperatives, LPDs, traditional markets, waste banks and BUMDES of Cepaka Village.